Fault Identification Based on Tulungagung Magnetic Anomaly Map - Kurniawati, Nur Laily; Muhardi, Muhardi; Perdhana, Radhitya (BERKALA SAINSTEK, 2024)
Tulungagung and Trenggalek are two regencies located south of Java Island with quite complex geological conditions because they are located in the Southern Mountains area. This study aims to identify the presence of faults based on the magnetic anomaly value of the Tulungagung sheet. The presence of faults at the research site were determined based on three lines on the regional magnetic anomaly using First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) derivative analyses. The results show that the regional magnetic anomaly is -210.7 nT to 113.2 nT. Line A-A' identified two fault locations at a distance of 15 km and 27 km from the line's starting point. Line B-B' identified three fault locations at a distance of 4 km, 27 km, and 45 km from the line's starting point. Line C-C' identified three fault locations at 10 km, 22 km, and 42 km from the line's starting point. The interpretation results also obtained subsurface lithology in the Alluvium Formation, Arjosari-Mandalika Formation, Wungkal Limestone Formation, and Malihan Rock Formation.